Legal knowledge and information systems : JURIX 2007 : the twentieth annual conference - Lodder, Arno R.; Mommers, Laurens, 1972- (Frontiers in artificial intelligence and applications ;, 2007)
This book includes papers from the twentieth JURIX conference (first organized in 1988). Over the years JURIX has become more and more international. JURIX is originally a Dutch/Belgian initiative. Nowadays, the conference papers are in majority from non-Dutch authors, and since 2002 JURIX is held outside the Netherlands and Belgium every other year. Most accepted papers can largely be fitted into either work on argumentation or work on ontology. Argumentation has been a JURIX-topic during all past years, and the interest in ontology has revived recently with Semantic Web initiatives. The topic.